2019
DOI: 10.1042/bsr20190955
|View full text |Cite
|
Sign up to set email alerts
|

Association of SP1 rs1353058818 and STAT3 rs1053004 gene polymorphisms with human tongue squamous cell carcinoma

Abstract: Objective: To study the association between SP1 rs1353058818 and STAT3 rs1053004 gene polymorphisms and risk of human tongue squamous cell carcinoma (TSCC). Methods: Sanger sequencing was used to determine the genotypes of SP1 rs1353058818 and STAT3 rs1053004 loci in 240 TSCC patients and 240 controls. Levels of hsa-miR-149-5p and hsa-miR-21-5p and expression levels of SP1 and STAT3 proteins in tumor tissues and adjacent normal tissues of TSCC patients were ascertained. Results: C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 27 publications
1
12
0
6
Order By: Relevance
“…Notably, our mechanistic experiments confirmed that the variant stat3 RNA derived from rs1053004-rs1053005 T-A haplotype indeed reduced stat3 expression perhaps due to the variant structure itself in the reporter gene-expression system. Our extensive findings are in line of the other report demonstrating that cancer patients with STAT3 SNP rs1053004 TT genotype expressed lower STAT3 protein as detected by Western blotting when compared to those with CC genotype (Lai et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Notably, our mechanistic experiments confirmed that the variant stat3 RNA derived from rs1053004-rs1053005 T-A haplotype indeed reduced stat3 expression perhaps due to the variant structure itself in the reporter gene-expression system. Our extensive findings are in line of the other report demonstrating that cancer patients with STAT3 SNP rs1053004 TT genotype expressed lower STAT3 protein as detected by Western blotting when compared to those with CC genotype (Lai et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…Since germline deletion of STAT3 in mice results in an early embryonic lethality ( Takeda et al., 1997 ), Cre-loxP recombination system to ablate the mouse STAT3 gene in later life emerged as a complex/unpractical tool to assess STAT3 for biological roles. However, in the setting of human diseases, STAT3 SNP analysis appears to be important and practical for studies of cancers and virus infections/diseases ( Eto et al., 2013 ; Xie et al., 2013 ; Moazeni-Roodi and Hashemi, 2018 ; Lai et al., 2019 ). In the current study, we employed a combination of STAT3 SNP analysis and mechanistic experiments in humans and cellular models, because the identified STAT3 SNP and relevant functions can be evaluated and characterized in cellular models with gene-targeted manipulations including short-term STAT3 knock-down ( Shen et al., 2017 ; Shen and Chen, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, miR‐149 is down‐regulated in head and neck squamous cell carcinoma and associated with the poor prognosis of patients 14 . In addition, miR‐149‐5p expression is decreased in oral cancer, like tongue squamous cell carcinoma and OSCC 15,16 . Moreover, miR‐149‐5p represses cell proliferation, migration, and invasion in OSCC via regulating transforming growth factor‐β2 (TGFβ2) 16 .…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the data demonstrated that miR-149-3p overexpression reduced the viability and colony formation of OSCC cells, whereas knockdown of miR-149-3p induced the proliferation of OSCC cells. Recent studies have revealed that lower levels of miR-149-5p were observed in OSCC tumor tissues compared with in adjacent normal tissues ( 28 ), whereas miR-149-5p overexpression resulted in attenuated proliferation and motility, as well as increased drug sensitivity, in OSCC cells ( 29 ). These data, together with the present findings, indicated the tumor-suppressive functions of miR-149-5p and miR-149-3p in OSCC, and suggested that the dual strand of miR-149 may be a potential biomarker for the generation and development of OSCC.…”
Section: Discussionmentioning
confidence: 99%